Development of research competence in education: systematic literature review.: Development of research competence in education: systematic literature review. - Suárez Orellana, Arturo Nicanor (2024)
The modern world demands better prepared people; that is to say, people who can handle different competencies; in this framework, research competencies are the ones that make it possible to continue developing other competencies; basic and higher education are the most appropriate stages to strengthen them. The objective of this research is to address the development of research competencies in the educational process. The methodology of systematic literature reviews has been followed, which have allowed addressing the topic in a broad manner and, at the same time, synthesizing it in this work. The results found show that the development of research competencies has been studied mainly in higher education and, mostly at the university level; to a lesser extent, at the basic education level. It is thus demonstrated that research competencies allow strengthening other competencies that contribute to a better performance in the work environment of future professionals, however, at an early age, it is not cemented.